Tres himnos patrios: El perfil del costarricense y la herencia cultural: una mirada a través de sus himnos - Carvajal Araya, María Isabel (2013)
The following work performs a view of the historical profile of the Costa Rican citizen, through the speech that lies within the lyrics of three Patriotic Anthems of Costa Rica, which were created in different time periods, hence, each owns different speech ideologies, despite all of them presenting relationships with other texts such as The Declaration of Man and Citizen’s Rights, of 1797, and the Proclama of Juan Rafael Mora, of 1855.